Analisis Tingkat Kesehatan Bank Menggunakan Metode RGEC pada Bank Syariah Tahun 2021-2023 - Kusumaningrum, Dwi; Suharto, Babun; Rahayu, Sri; Setiadi, Pompong B (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
In developed and developing countries, people really need a bank as a place or place to conduct financial transactions. The community assumes that banks are the safest financial institutions in carrying out various financial activities. Meanwhile the community must ensure that the bank used is healthy, stable and safe so that the community does not lose. For banks, bank health is important to shape public trust. Then the existing banks in Indonesia really need to set bank health rules. Indonesian Islamic Bank is the result of a merger from three Islamic banks owned by BUMN, namely Syariah Mandiri Bank, BNI Syariah and BRI Syariah. Indonesian Islamic Bank was established on February 1, 2021. This study has the aim to find out the health level of Indonesian Islamic banks in 2021-2023 with the RGEC method. The analysis method in research uses a descriptive quantitative approach. The results of this study indicate that the Indonesian Islamic Bank NPF is below 2% which means in a "very healthy condition. FDR ratio in 2021 amounted to 73.39% with" very healthy "conditions, while FDR in 2022-2023 results of the ratio of more than 75% to less 85% which means in a" healthy condition. The GCG ratio is in "quite healthy" conditions. The ROA ratio of 2021-2023 is not less than 1.25 and no more than 2% means in a "healthy" condition, while in 2023 in a "very healthy" condition. Ratio and ROE ratios in 2021-2023 are in "healthy" conditions. The ROA and ROE ratio in 2021-2023 is in a "very healthy" condition.